Proses Produksi Iklan Radio di LPP Radio Republik Indonesia Palu - Dyah Fitria Kartika Sari; Achmad Herman; Sitti Murni Kaddi (Universitas Muhammadiyah Sidoarjo, 2017)
This study aimed to determine types of advertising which is produced in LPP RRI Palu and its production process as well as determine supporting and inhibiting factors of radio advertising production process. The methodology used Action Research based on model characteristics, organizational structure and development goals, system design or scientific development and form of research involvement. The results showed that advertisement was produced in LPP RRI Palu was ad lib, ad spot, and sponsor program. Ad lib production process that was initial briefing, editing script, and broadcast. Ad spot was the initial briefing, creative strategy formulation, drafting, implementation, production of finished advertisement, and evaluation. While ad sponsors program was collaboration of ad spots and ad lib that aired alternately during one program of the event took place. Percentage for ad lib 50% and spot ads 50% per time of ad broadcast. Whereas the program sponsor's only has one or two even in one year there was no broadcast sponsor program. Overall ad impressions per day account for 15% of all broadcast programs.